Do Self-Reported Psychopathic Traits Moderate the Relations Between Delinquent History Predictors and Recidivism Outcomes in Juvenile Delinquents? - Pechorro, Pedro (2022)
The present study investigates whether self-reported psychopathic traits moderate the relationships between delinquent career features (i.e., age of first detention in a juvenile detention center, crime frequency, crime diversity, crime charges, and Conduct Disorder) and 1-year general delinquency and violent delinquency recidivism outcomes. The sample was composed of male youth (N = 214, M = 16.4 years, SD = 1.3 years) originating from the juvenile detention centers managed by the Ministry of Justice of Portugal. Results mostly suggest that neither the Antisocial Process Screening Device––Self-Report total score nor its Callous-Unemotional, Impulsivity, and Narcissism factor scores moderate the relationships between the delinquent career variables and general and violent delinquency recidivism outcomes. The notable exception was the interaction between crime frequency and callous-unemotional traits in predicting general recidivism. The current findings question the relevance of self-reported psychopathic traits as moderators of recidivism among juveniles despite the general association between psychopathy and conduct problems among youth